Metafiction in Anton Chekhov’s "A Story Without an End" - Artur Sadecki (Zeszyty Cyrylo-Metodiańskie)
The paper seeks to explore how the metafictional awareness within each character shapes the overall interpretation of “A Story Without an End” (1886) by Anton Chekhov. From this perspective, this short story can be seen as Chekhov’s commentary on his own writing, revealing the path of evolution he would take in the years that followed. The analysis leads to the conclusion that “A Story Without an End” should be regarded as one of the key texts in the author’s creative breakthrough period, since after 1886 Chekhov’s works evolve towards greater artistic challenges and a style that goes far beyond the norms of humorous writing. Original title in Polish: Metafikcja w „Opowiadaniu bez końca” Antoniego Czechowa.